Predictive intelligence using big data and the internet of things - Gupta, P. K. 1976-; Oren, Tuncer I.; Singh, Mayank 1982- (IGI Global, 2019)
"This book provides state-of-the-art research on big data and the Internet of Things (IoT), along with other related areas to ensure efficient and Internet-compatible IoT systems. It discusses various issues related to big data security and privacy challenges along with energy-efficient approaches to improve virtual machine placement in cloud computing environments"..